The aging lung: microenvironment, mechanisms, and diseases - Wang, Yanmei; Huang, Xuewen; Luo, Guofeng; Xu, Yunying; Deng, Xiqian; Lin, Yumeng; Wang, Zhanzhan; Zhou, Shuwei; Wang, Siyu; Chen, Haoran; Tao, Tao; He, Lei; et al. (Frontiers in Immunology, 2024)
With the development of global social economy and the deepening of the aging population, diseases related to aging have received increasing attention. The pathogenesis of many respiratory diseases remains unclear, and lung aging is an independent risk factor for respiratory diseases. The aging mechanism of the lung may be involved in the occurrence and development of respiratory diseases. Aging-induced immune, oxidative stress, inflammation, and telomere changes can directly induce and promote the occurrence and development of lung aging. Meanwhile, the occurrence of lung aging also further aggravates the immune stress and inflammatory response of respiratory diseases, the two mutually affect each other, and promote the development of respiratory diseases. Explaining the mechanism and treatment direction of these respiratory diseases from the perspective of lung aging will be a new idea and research field. This review summarizes the changes in pulmonary microenvironment, metabolic mechanisms, and the progression of respiratory diseases associated with aging.